2009
DOI: 10.1177/0265407509345653
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment and romantic partner preference: A review

Abstract: In this literature review we explore inconsistencies in studies relating self-reported adult attachment to romantic partner preference. Such studies have tested one of three hypotheses: that individuals prefer partners with a similar attachment style, a complementary attachment style, or the attachment style most likely to offer attachment security. Consistent with all hypotheses, secure individuals prefer similarly secure partners. Discrepancies are found, however, regarding insecure individuals' preferences.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
77
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 50 publications
13
77
0
4
Order By: Relevance
“…Avoidant-dismissing individuals are characterised by high avoidance and low anxiety. While they have a positive model of the self, they have a negative evaluation of others as depending and needy, perhaps reflecting their discomfort with intimacy [21]. Anxious-preoccupied individuals are characterised by high anxiety and low avoidance, view themselves as unworthy and are preoccupied with the need to be accepted by others [20] [21].…”
Section: Theoretical Issues In Attachment Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Avoidant-dismissing individuals are characterised by high avoidance and low anxiety. While they have a positive model of the self, they have a negative evaluation of others as depending and needy, perhaps reflecting their discomfort with intimacy [21]. Anxious-preoccupied individuals are characterised by high anxiety and low avoidance, view themselves as unworthy and are preoccupied with the need to be accepted by others [20] [21].…”
Section: Theoretical Issues In Attachment Researchmentioning
confidence: 99%
“…Using this model combined with Brennan et al's [19] anxiety and avoidance dimensions, more recent research assessed attachment style as being continuous rather than categorical in nature [47] [48]. While these approaches are all highly related, attachment classifications across measures do not always correlate [8] [21]. Both the categorical and dimensional approaches are meaningful ways of looking at attachment and one has not been found to be more powerful than the other [49] [50].…”
Section: Theoretical Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding someone to share life with in a long lasting and stable partnership is a key social process, many adults aim to establish (Holmes & Johnson, 2009). Romantic relationships play a central role in adults" lives and are associated with all kinds of outcome, such as wellbeing (Musick & Bumpass, 2012;Soons & Liefbroer, 2008;Soons, Liefbroer, & Kalmijn, 2009), health (Musick & Bumpass, 2012), and mortality (Drefahl, 2012).…”
Section: Romantic Relationsmentioning
confidence: 99%
“…On the one hand, there are some studies where the structural coupling hypothesis among secure individuals seems to have been confirmed, with little proof of romantic relationships which are characterized, even at the level of preference, from anxious-anxious and avoidant-avoidant coupling in respect to avoidant-ambivalent coupling (e.g. Collins & Reed, 1990;Kirkpatrick & Davis, 1994;Pietromonaco & Carnelley, 1994;Holmes & Johnson, 2009;Strauss et al 2012). On the other hand, other studies have shown inconsistencies in respect to the theory.…”
Section: From Behavioral Attachment System To Structural Couplingmentioning
confidence: 99%